Clinical and gender differences in heart transplant recipients in the NEW HEART study. (March 2017) - Hickey, Kathleen T; Doering, Lynn V; Chen, Belinda; Carter, Erik V; Sciacca, Robert R; Pickham, David; Castillo, Carmen; Hauser, Nicole R; Drew, Barbara J
Background: Little attention has focused on gender differences in cardiac comorbidities and outcomes in patients undergoing orthotropic heart transplant. Objective: The objective of this study was to investigate gender differences at baseline and during follow-up among heart transplant patients. Methods: An observational cohort within the NEW HEART study was evaluated to determine gender differences in relation to age, coexisting cardiac comorbidities, and outcomes. Differences were assessed by t -test, Fisher's exact test, and logistic regression analysis. Results: Male transplant recipients ( n  = 238) were significantly older than female recipients ( n  = 92), with a greater percentage over 60 years of age (45% vs. 24%, p  = 0.0006). Males were more likely to have hypertension (63% vs. 49%, p  = 0.034), dyslipidemia (62% vs. 45%, p  = 0.006), a history of smoking (52% vs. 35%, p  = 0.009), and diabetes (42% vs. 21%, p  = 0.0002). Analysis of endomyocardial biopsies obtained during the 1-year follow-up period demonstrated that women averaged more episodes of acute rejection than men (3.9 vs. 3.0, p  = 0.009). While most episodes of rejection were mild, women were more likely than men to have episodes of moderate or severe rejection (14% vs. 5%, p  = 0.012) and to be hospitalized for acute rejection (15% vs. 6%, p  = 0.013). There were no significant differences in mortality. Conclusions: Men were more likely than women to be older and to have diabetes, dyslipidemia, hypertension, and a history of smoking. Women were more likely to experience moderate or severe allograft rejection and to be hospitalized for acute rejection. Future investigation of the reasons for these gender differences is warranted and may improve clinical care of women undergoing cardiac transplantation.